Prevalence of disordered eating in elite female athletes in team sports in Greece - Kampouri, D.; Kotopoulea-Nikolaidi, M.; Daskou, S.; Giannopoulou, I. (European Journal of Sport Science, 2019)
The purpose of the study was to assess (a) the prevalence of disordered eating (DE) in elite female team sports players compared to non-athletes and (b) to compare DE prevalence in elite female players in basketball, volleyball and water polo. One hundred and seventy-five females were recruited (age 23.10 ± 5.4, BMI 21.85 ± 2.3 kg/m2), 53 were elite basketball players, 42 were elite volleyball players, 34 were elite water polo players and 46 were non-athletes. Participants completed the Eating Disorders Questionnaire (EDE-Q) and a physical activity questionnaire. The EDE-Q incorporates 36 statements which relate to the occurrence and frequency of key behaviours of eating disorders, under the following four subscales: Restraint, eating concern, shape concern and weight concern and a global score of disordered eating. No differences were found in the EDE-Q subscale score and global score between athletes and non-athletes. Only 6.2% of the total number of participants exhibited DE using the global score >2.3. Water polo players had significantly higher scores in the `eating concern` subscale and in the frequency of key behavioural features of DE such as binge eating episodes and objective and subjective bulimic episodes, compared to volleyball and basketball players. In conclusion, team sport elite female players do not exhibit greater prevalence of DE compared to non-athletes. Water polo, a sport that emphasises leanness and control of body weight for international distinctions, is associated with a higher tendency to exhibit DE, when compared to other team sports.